Characterization on eye glass bead found at Khao Sri Vichai (Surat Thani), Thailand - K. Won-In (2018)
It was known that eye glass beads originated in the Near East during the mid 2 nd millennium BC and spread to Mediterranean and Asia. In Thailand, they have been found at various archaeological sites in southern areas, especially the ancient maritime ports. In this work, Scanning electron microscope coupled with energy dispersive X-ray fluorescence spectroscopy (SEM-EDS), proton induced X-ray emission spectroscopy (PIXE), micro-beam X-ray fluorescence spectroscopy based on synchrotron radiation (μ-SRXRF) and Raman spectroscopy were carried out to characterize the composition of the eye-glass bead which excavated from Khao Sri Vichai at Surat Thani Province. It has a black body, dark blue pupil and ochre circle pattern on the inlaid white eyeball. It was found that its shape was similar as those which were unearthed from the ancient tombs of the Early Warring State Period (∼500 B.C.) at China. The main compositions were alkali-silicate glass. Surface microstructure has been found to be corroded. This data was one of the evidences which confirmed the ancient long distance trade or exchange network. © 2013 The Authors.